Direction modulation based on non‐linear frequency diverse array. Issue 22 (20th July 2021) - Guo, Rujiang; Liu, Huijie; Zhao, Lingfeng; Ni, Yinghong
Abstract: A design method of non‐linear frequency diverse array is presented to generate the desired direction modulation for the array. The proposed method firstly sets the desired direction modulation, and then forms the desired transmit beampattern by adjusting the frequency of each array element in a non‐linear manner. Theoretical analysis and numerical experiments have verified the effectiveness of the proposed method.